2019
DOI: 10.1159/000497228
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Iron Levels Interaction with Central Obesity on the Risk of Nonalcoholic Fatty Liver Disease: A Case–Control Study in Southeast China

Abstract: Objectives: We aimed to evaluate the associations between body iron stores and the risk of nonalcoholic fatty liver disease (NAFLD) in a Chinese population and explore whether this effect may be modified by other factors. Methods: A 1: 1 frequency-matched case–control study was conducted, including 482 NAFLD cases and 490 gender- and age-matched controls. Serum levels of ferritin, hepcidin, and C-reactive protein were measured. Results: Multivariate logistic regression analysis showed that hepcidin was not ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 34 publications
(44 reference statements)
1
24
0
Order By: Relevance
“…In line with our results, Ryan et al reported a strong association between ferritin and hepatic iron content by MRI in 129 participants with NAFLD [39]. Scientific evidences have shown that increased iron stores are intimately connected to β-cell dysfunction, impaired glucose metabolism, type 2 diabetes, DNA damage, and lipid peroxidation [24,36,37]. The main mechanism proposed is that iron promotes oxidative stress reactions resulting in cellular damage [14,15].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with our results, Ryan et al reported a strong association between ferritin and hepatic iron content by MRI in 129 participants with NAFLD [39]. Scientific evidences have shown that increased iron stores are intimately connected to β-cell dysfunction, impaired glucose metabolism, type 2 diabetes, DNA damage, and lipid peroxidation [24,36,37]. The main mechanism proposed is that iron promotes oxidative stress reactions resulting in cellular damage [14,15].…”
Section: Discussionsupporting
confidence: 89%
“…Hepatocytes constitute the major parenchymal iron storage pool and contain large amounts of ferritin, the primary iron storage protein [35]. Iron is an essential but potentially toxic element that may promote the onset and progression of NAFLD by increasing oxidative stress and altering insulin signaling and lipid metabolism [14,15,36,37]. Iron overload is observed in approximately one-third of adults with NAFLD [38].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it's plausible that increased hepatic lipid accumulation and insulin resistance play a substantial role in the relationship of meat intakes with the development of NAFLD. In addition, a study by Avila et al found that red meat was positively relevant to serum ferritin [32], which can increase the risk of NAFLD [33,34]. Fried food will produce some hazardous chemicals, such as advanced glycation end products and trans fatty acids [35,36], which were reported to play a critical role in NAFLD [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…However, in inflammatory conditions ferritin concentrations are increased and it is synthesized as an acute phase protein, acting as a pro-inflammatory molecule capable of inducing liver damage. [33,35,36,37]. The potential anti-inflammatory effect and antioxidant capacity of omega-3 PUFAs [38], might ameliorate ferritin pro-oxidant and pro-inflammatory activity, although the exact molecular pathways are yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the principal iron-storage organ and plays a central role in iron metabolism [4,35]. Increased hepatic iron concentrations are associated with metabolic alterations including insulin resistance and type 2 diabetes [15].…”
Section: Discussionmentioning
confidence: 99%